2018
DOI: 10.15296/ijwhr.2019.09
|View full text |Cite
|
Sign up to set email alerts
|

The Psychometric Properties of the Persian Version of the Pregnancy Physical Activity Questionnaire

Abstract: Objectives: Evidence indicates that regular physical activity has positive effects on the mother’s health and outcomes of pregnancy. The measurement of physical activity during pregnancy is required for planning and developing health-related interventions. The aim of this study was to evaluate the psychometric properties of the Persian version of the pregnancy physical activity questionnaire. Materials and Methods: This cross-sectional methodological study was conducted with a sample of 200 pregnant women livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Furthermore, according to the Koo and Mae guidelines [ 29 ], the current study had strong test–retest reliability, with ICCs ranging from 0.768 to 0.930. This result is comparable with previous translations and adaptations of the PPAQ, such as those by Danes, Persians, and Vietnamese, as well as the original version [ 25 , 34 , 35 , 40 ]. Based on the activity categories, the reliability results were good for all types of activities except caregiving, which was excellent.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, according to the Koo and Mae guidelines [ 29 ], the current study had strong test–retest reliability, with ICCs ranging from 0.768 to 0.930. This result is comparable with previous translations and adaptations of the PPAQ, such as those by Danes, Persians, and Vietnamese, as well as the original version [ 25 , 34 , 35 , 40 ]. Based on the activity categories, the reliability results were good for all types of activities except caregiving, which was excellent.…”
Section: Discussionsupporting
confidence: 88%
“…The ICC for occupational activity in our study showed good reliability, as it did in the studies of Chinese, Spanish, Vietnamese, Persians, and Poles [ 34 , 40 , 41 , 42 , 43 ]. In addition, the ICCs for household activity and sports/exercise activity showed good reliability, which was in line with other studies [ 34 , 35 , 40 , 42 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In EFA, factors with eigenvalues greater than 1.5 were considered as the major factors (53). The minimum value of α was considered 0.7 (54). SPSS software version 22 and LISREL version 8.8 were used for data analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire is completed through a telephone interview in the rst and third trimester (between 32-36 weeks of pregnancy) of pregnancy. The Persian version of the questionnaire has good reliability, with an ICC coe cient of 0.87 and a Cronbach's alpha coe cient of 1.69 (70). In this study, the questionnaire's reliability will be assessed using Cronbach's alpha.…”
Section: Physical Activity Questionnaire In Pregnancy (Ppaq)mentioning
confidence: 99%